Program Penyiaran Berita TVRI Era Orde Baru (1975-1998) - Putri, Mayang Anugraheni Nindya; Dewi, Ita Mutiara (Historia Madania: Jurnal Ilmu Sejarah, 2025)
This research aims to examine the dynamics of TVRI news program broadcasting in the New Order era, precisely from 1975-1998. This article explains how TVRI's news coverage during the New Order era, government policies towards the broadcasting of TVRI's news programs, and how Indonesian people criticized TVRI's news at that time. This research uses a research method in the form of a historical research method that begins with the collection of historical sources or heuristics, criticism of historical sources or verification, interpretation of historical sources or interpretation, and the last is historical writing or historiography. The results of this study show that most of TVRI's news broadcasts during the New Order period tended to be more inclined to the government. The government's policies towards TVRI news broadcasts were very strict, including strict news control and filtering. Many Indonesians then criticized TVRI's programs, and many of them switched to enjoying news broadcasts on private television. Keywords: TVRI, news, television